2017
DOI: 10.1590/1980-5373-mr-2017-0406
|View full text |Cite
|
Sign up to set email alerts
|

Production of TiO2 Coated Multiwall Carbon Nanotubes by the Sol-Gel Technique

Abstract: In recent years, efforts in developing high strength-low density materials are increasing significantly. One of the promising materials to attend this demand is the carbon nanotube (CNT), to be used mainly as a reinforcing phase in lightweight metal matrix composites (MMC). In the present work, the sol-gel technique has been employed to obtain TiO 2 coating on the surface of commercial multiwall carbon nanotubes (MWCNT). The aim of such coating is to improve the thermal stability of MWCNT in oxidize environmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 42 publications
(38 reference statements)
1
12
0
Order By: Relevance
“…The MWCNT support was thermally stable up to 500 C, while Ni 10 -Mn 10 /MWCNT, Ni 10 -Cu 10 /MWCNT, Ni 10 -Mg 10 /MWCNT and Ni 10 -Ce 10 /MWCNT showed weight loss changes at 400 C. The weight loss within the temperature the range 400-650 C is typically due to the oxidation of MWCNTs. 36 The reduction in thermal stability of MWCNTs by incorporation of binary metal oxide promoters is due to the presence of structural imperfections (vacancies and dislocations). 37 The Ni 10 -Mg 10 / MWCNT showed additional weight losses at a lower temperature (<300 C), which is attributed to the vaporisation of physically adsorbed water.…”
Section: Characterisation Of the Catalystsmentioning
confidence: 99%
“…The MWCNT support was thermally stable up to 500 C, while Ni 10 -Mn 10 /MWCNT, Ni 10 -Cu 10 /MWCNT, Ni 10 -Mg 10 /MWCNT and Ni 10 -Ce 10 /MWCNT showed weight loss changes at 400 C. The weight loss within the temperature the range 400-650 C is typically due to the oxidation of MWCNTs. 36 The reduction in thermal stability of MWCNTs by incorporation of binary metal oxide promoters is due to the presence of structural imperfections (vacancies and dislocations). 37 The Ni 10 -Mg 10 / MWCNT showed additional weight losses at a lower temperature (<300 C), which is attributed to the vaporisation of physically adsorbed water.…”
Section: Characterisation Of the Catalystsmentioning
confidence: 99%
“…It is known that D and G bands of carbon structures are located at ca. 1350 and 1600 cm −1 , and G band is common for all sp2 carbon forms giving information on the in-plane vibration of sp2 bonded carbon (tangential stretching mode of C=C bond), whereas D band is associated with structural disorder (the presence of sp3 defects) [19,44]. Therefore, it was confirmed that TiO 2 (C) was surface modified with carbon species, correlating well with high absorption at vis range (Figure 3a).…”
Section: Characterization Of Samplesmentioning
confidence: 64%
“…Unfortunately, it was difficult to detect two characteristic peaks for graphene-kind structure at ca. 1304-1349 cm −1 and 1588-1601 cm −1 (as reported for graphene, GO, rGO, multiwall carbon nanotubes (MWCNT) of graphitic nature [19,20,23,44]), probably due to its low content. Interestingly, low-intensity peaks at ca.…”
Section: Characterization Of Samplesmentioning
confidence: 71%
“…Furthermore, the analysis period is also relatively short [43,[102][103][104]. It seems that the absorption peaks at 1340, 1582, and 2670 cm −1 corresponded to the D, G, and 2D band modes, respectively, which were clearly observed in the Raman spectra of solution product, where the D band exhibits disordered carbon mode and the G band exhibits ordered carbon mode [105,106]. Obviously, the absorption peak at around 2920 cm −1 , which was associated with the hydroxyl group, was also found in this Raman spectrum [107][108][109].…”
Section: 4 For Peermentioning
confidence: 99%